Photocatalytic Degradation of Methyl Violet with TiSiW12O40/TiO2. (16th April 2013) - Yang, Shuijin; Xu, Yulin; Huang, Yongkui; Zhou, Guohui; Yang, Zhiyuan; Yang, Yun; Wang, Guohong
Abstract : The photocatalytic degradation of methyl violet using TiSiW12 O40 /TiO2 as a novel eco-friendly catalyst under simulated natural light irradiation was investigated. The physical characterizations were carried out by TG/DTA, FT-IR, XRD, and UV-visible spectra. The effects of the initial methyl violet concentration, the solution pH, and catalyst dosage on the photocatalytic degradation rate of methyl violet were also examined. The results demonstrated that at optimal condition (initial concentration of methyl violet is 20 mg/L, catalyst dosage is 0.3 g, and the pH is 5.5), the degradation rate of methyl violet is as high as 82.4% after 3 h under simulated natural light irradiation. The reaction of photocatalysis for methyl violet can be expressed as first-order kinetic model.